PEDAGOGICAL TESTING AS A MEANS OF EDUCATIONAL MONITORING: MANAGEMENT ASPECT - Charkina, O.A. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem concerning existing possibilities of pedagogical testing while forming monitoring system of education establishments on managers’ level.